The Effect of Institutional Quality on Banking Performance in Emerging Countries - Halaç, Umut; Durak, Mustafa Gürol; Çelik, İlyas (Panoeconomicus, 2024)
Banks play a crucial role in the economy and improving their performance leads to healthier economic activities. Therefore, the methods of efficiently measuring bank performance need to be highlighted. The "CAMELS" rating system has become the most comprehensive and contemporary measurement method in this context. Various factors, both bank-specific and country-specific, affect bank performance. Among these factors, the Worldwide Governance Indicators reflect the public's perception of institutional quality, a proxy for country-specific factors. This study aims to analyze the impact of the Worldwide Governance Indicators on bank performance, using a sample of 1649 banks in 26 emerging countries within the 2008-2018 period. The system GMM results demonstrate that these indicators significantly affect banking performance in different aspects and directions. JEL: G18, C33, C55.